2019
DOI: 10.1111/scs.12781
|View full text |Cite
|
Sign up to set email alerts
|

Early integration of palliative care: translation, cross‐cultural adaptation and content validity of the Supportive and Palliative Care Indicators Tool in a Swedish healthcare context

Abstract: Background Timely identification of patients with palliative care needs is a prerequisite for being able to carry out effective and equal palliative care. The Supportive and Palliative Care Indicators Tool (SPICT) identifies patients likely to benefit from a palliative approach. Aim The main objective was to describe the translation, cross‐cultural adaptation and content validation process of the SPICT‐SE. In this process, the prefinal SPICT‐SE was tested in focus group interviews to explore how the tool was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Furthermore, themes 1, 2, and 3 indicate that SPICT ™ -DK has the potential to be used as a linguistic framework for supportive and/or palliative care and a collaborative and pedagogical tool among different professional groups and health care settings. In line with a Swedish study [19], our findings indicate that SPICT ™ -DK has potential in terms of when to take a breakpoint conversation with the patient and the family about future treatment and care.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, themes 1, 2, and 3 indicate that SPICT ™ -DK has the potential to be used as a linguistic framework for supportive and/or palliative care and a collaborative and pedagogical tool among different professional groups and health care settings. In line with a Swedish study [19], our findings indicate that SPICT ™ -DK has potential in terms of when to take a breakpoint conversation with the patient and the family about future treatment and care.…”
Section: Discussionsupporting
confidence: 88%
“…SPICT ™ can be used for all patients, in all contexts, and at any point in the disease trajectory [16,17]. At present, SPICT ™ has been translated into 10 languages [15], for example, German [18], Swedish [19] Italian [20], and Spanish [21], and has been shown to identify people with deteriorating health and those in need of palliative care [22]. For example, studies show that the tool can be useful as a support in clinical decision-making in hospitals to identify patients in need of palliative care [16] and can be used to identify older hospitalized patients at risk of dying within a year [23].…”
mentioning
confidence: 99%
“…The use of SPICT has also been shown to provide patients with a better quality of life and to involve family members [34]. SPICT has been translated into Swedish with a cross-cultural adaptation, and it has been shown to be well designed with all the indicators for palliative care [35]. Therefore, the SPICT instrument may be a better instrument for identifying patients with serious illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…In the general population, IPOS and SPICT have the best evidence of validity, reliability, and practicality [55,65,72,73,[78][79][80][81][82][83][84], followed by NECPAL and RADPAC [60,66], while no formal validation studies were found for GSF-PIG.…”
Section: Comparing the Psychometric And Practicality Properties Of Thmentioning
confidence: 99%